Body fat ratio as a novel predictor of complications and survival after rectal cancer surgery - Zhao, Haiyuan; Liu, Gang; Li, Yang; Lu, Feixiang; Yang, Nianzhao; Zhao, Jun (Frontiers in Nutrition, 2024)
The present study aimed to evaluate the association between body fat ratio (BFR), visceral fat area (VFA), body mass index (BMI) and visceral fat density (VFD) and assess their reliability in assessing risk of postoperative complications and survival status in patients with rectal cancer (RC).The present study retrospectively included 460 patients who underwent surgical treatment for RC at the First Affiliated Hospital of Wannan Medical College (Yijishan Hospital of Wannan Medical College, Wuhu, China) between September 2018 and July 2021. BFR, VFA, BMI, and VFD were measured and basic information, clinical data, complications and survival were recorded.Results: Statistical analysis was performed to determine optimal BFR cut-off and evaluate group differences. BFR demonstrated a significant positive correlation with VFA (R=0.739) and BMI (R=0.783) and significant negative correlation with VFD (R=-0.773). The areas under the receiver operating characteristic curve of BFR, VFA, BMI and VFD in predicting postoperative complications in RC were all >0.7 and the optimal cut-off value of BFR was 24.3.Patients in the BFR-low group had fewer postoperative complications, lower intraoperative indices, shorter hospitalization times and lower costs than those in the BFR-high group. BFR predicted complications with high diagnostic significance and was validated by multiple models. Furthermore, patients in the BFR-high group had a longer overall survival compared with patients in the BFR-low group.BFR was associated with BMI, VFA and VFD. A BFR threshold of 24.3 was correlated with decreased complications and enhanced long-term survival.